Trends and variability in local abundances of sailfish Istiophorus platypterus in Pacific waters of Costa Rica: Controls and effects on recreational fisheries - Marrari, Marina; Chaves-Campos, Johel; Mug Villanueva, Moisés; Martínez-Fernández, Damián; Marín Sandoval, Henry; Staley Meier, Todd (Frontiers in Marine Science, 2023)
Fishing tourism represents a vital industry in Costa Rica, generating over US$520 million and attracting 150,000 tourists every year. The main objective of this study is to examine trends and variability in local abundances of sailfish Istiophorus platypterus, the main sportfish in Pacific waters of Costa Rica, and quantify the influence of environmental and anthropogenic factors. We compiled and analyzed sailfish information collected from sportfishing operations. Sailfish abundances were examined in relation to environmental conditions and commercial fishing. Timeseries analyses showed significant declining trends in local abundances of sailfish in the southern and central Pacific of Costa Rica over the last decade. Bycatch records from the commercial purse seine fleet operating in Costa Rican waters also show a declining trend in sailfish numbers. On the other hand, commercial landings from the national longline fleet show a significant increase of 108%, on average, over the past decade. Different numerical models indicated that fishing pressure from the national fleet and also sea surface temperature with different time lags affect local abundances of sailfish. While other countries in Central and North America protect sailfish and other species of tourist interest, Costa Rica still allows the landing and sales of billfishes as seafood. The results presented in this study highlight the need to allow for the recovery of local abundances of sailfish and promote the development of the coastal communities that depend on marine tourism as their main source of income.